The Effect of GlobalWarming on Tea Production. Case Study of PTPN XYZ in Indonesia - Indahsari, G.; Kesumajaya, D.; Kesumajaya, D. (European Scientific Journal, ESJ, 2017)
National consumption for tea in Indonesia is about 145 thousand (tonnes) annually with an increasing rate of 1.57 percent per year. Although the consumption rate has increased, national tea production has steadily declined over the last 10 years. Increasing temperatures due to climate change have been put forward as a contributing factor to the decline of tea production. In addition, the area of land used for tea production has decreased to make way for both housing development projects and other forms of cash crops. The conversion of land used for tea into other crops is in turn linked to increasing temperature and unstable weather conditions that aggravate tea production. Thus increases the cost of tea production and motivates tea plantations to switch to palm oil production or horticulture which produces higher profits. In this paper, PTPN XYZ of West Java, Indonesia is used as a case study to show the transition from tea production to alternative cash crops as a result of unsuitable weather conditions and its impact on decreasing national tea production.